Effectiveness Of Change Management During Joint Venture Formations For Software-Defined Vehicles In The Automotive Industry - Ahuja, Neetika (Digital Repository of Theses, 2025)
Advancements in software technologies are rapidly transforming the automotive landscape for software-defined vehicles. The research assesses the effectiveness of change management in a global automotive engineering organization involved with software-defined vehicles towards the formation of joint ventures. Through a mixed-method approach with a case study and follow-up survey, it examines the emotional state, challenges and barriers of change effectiveness, and factors that could smoothen the change initiative with participation from diverse levels from the organisation. The results indicate the different emotional stages between the higher management, middle management, and employees due to being at different stages/phases of the change. It is evident from the discourses that on a time scale the higher management will always have information ahead of others in the organisation, and the ease of transformation will be to bring the information flow from higher management to the rest of the organisation via middle management in a constructive, multidirectional approach with a good communication and implementation plan that addresses the day-to-day operational challenges faced by ground-level employees. Most often higher management is focused on the business outcomes, and there is a compelling need to also look at the people side of change. Absence of this imbalanced approach creates a disconnect between the employees and management, leading to a trust deficit. The findings also reflect that the employees largely believed in change, with most employees aligned to the strategic direction and vision of the organisation. Concerns were about how and when the change was being implemented. While the automotive space in the context of software-defined vehicles will go through alliances, joint ventures, and partnerships, the research opens up the potential to study further cultural shifts, integration of diverse ecosystems, legal framework impact, and evolution of new business models.